Analysis of the Narration Time of Beyzayi Works Based on the Views of Gerard Genette A Case Study of the Play “The Eighth Voyage of Sinbad” and Screenplays of “Facing Mirrors” and “Reed Curtain” - Ali Khorashadi; Meghdad Javid Sabaghian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Bahram Beizayi is one of the most important artists in the field of drama in Iran. Nevertheless, after nearly 60 years of Beizai's artistic activity, and in the tumult of opponents and proponents of his works, what can be seen and heard is about what he says, not how he says: from mythological and historical critiques to feminist and political critiques that interpret his works in the politics of the time. In this article, we try to examine 3 elliptical works including "The Eighth Voyage of Sindbad", "Reed Curtain" and "Facing Mirrors" from the perspective of narrative form. Elliptical screenplays are writings that are published before they can be made. From this perspective, we encounter a unique phenomenon that allows screenwriters to access, research and study the screenplay itself - even before the film is made. The way to explain and examine these works is to examine the narrative style and, in particular, the timing of the narrative, relying on the views of Gerard Genette, the French structuralist narrator. The purpose of this article is to study the relationship between time and causality as the basis of a narrative in Elliptical works and to explain how he views the universe, focusing on the form of his works.